Factors Influencing Hypertension Prevalence in Patients Attending Hypertensive Clinic in Siaya County Referral Hospital, Kenya - Owenga, Jane; Odhiambo, Judith; Olayo, Rose; Awiti, Leon (International Journal of Emerging Trends in Social Sciences, 2019)
This study focused on the factors influencing hypertension prevalence among patients attending a hypertensive clinic in Siaya County Referral Hospital. Cross-Sectional descriptive study design was employed and the researcher collected both qualitative and quantitative first-hand information from the key informants and hypertensive patients respectively. The study targeted 34o hypertensive patients attending the hypertensive clinic in the county hospital, Krejcie and Morgan sampling frame was used to arrive at a sample of181patients who were then obtained through simple random sampling. The study used key informant interview guides and questionnaires to collect the data. Quantitative data were analyzed descriptively using measures of central tendency, frequencies and percentages and inferentially through Spearman Correlation. Qualitative data were analysed through content analysis. The study found out that demographic characteristics and attitude on hypertension had an insignificant negative influence on hypertension prevalence. Knowledge and social-economic characteristics had significantly negative influence on the prevalence of hypertension. The study recommends that the government and the various agencies like the NGOs and mass media should intensify campaigns that are aimed at increasing the knowledge, awareness, education and information concerning hypertension and its effects. Finally, there is a need for both the county and the national government to come up with health support programs, including subsidized medicare, increasing free medical camps and provision of affordable health insurance covers that would cater for patients of low socio-economic status to enable them access medical care.